Development and Validation of a Digital Patient Guide to Clinical Photography for Teleconsultation in Dermatology (Global Journal of Medical Research, 2024)
Introduction: Dermatological teleconsultation requires patients to provide high-quality images of cutaneous lesions for accurate diagnosis and treatment. Patients assume a pivotal role in teledermatology by effectively documenting skin lesions using standardized photographs. This study aimed to develop and validate a digital guide to assist patients in adequately documenting cutaneous lesions for dermatological teleconsultations.
Keywords: telemedicine teledermatology remote consultation dermatology digital health clinical photography teleconsultation